Professional Practice in Facility Programming (Routledge Revivals). - Preiser, Wolfgang (Oxford : Taylor & Francis Group, 2014)
This compelling resource, which was first published in 1993, was the first book on facility programming to design parameters and specifications over a broad range of project types. Professional Practice in Facility Programming is a uniquely current, self-contained resource that will prove invaluable to a wide cross-section of practitioners and students.
Cover -- Half Title -- Title Page -- Copyright Page -- Original Title Page -- Original Copyright Page -- Table of Contents -- Preface -- Contributors -- Introduction -- PART I: NEW DEVELOPMENTS IN FACILITY PROGRAMMING -- Chapter 1 Strategic Asset Management: An Expanded Role for Facility Programmers -- Chapter 2 Applying the Problem-Seeking Approach to Engineering Programming -- Chapter 3 NCR Corporation Worldwide Facilities Design Guidelines -- Chapter 4 Facilities Managers and New Developments: The Experience of Broadgate and Stockley Park -- Chapter 5 Computer Usage in Facility Programming -- Chapter 6 Participatory Programming of Campus Child-Care Facilities -- Chapter 7 Programming Office Space: Adaptive Re-Use of the H-E-B Arsenal Headquarters -- PART II: PROGRAMMING CASE STUDIES -- Chapter 8 Interior Programming, Stacking, and Blocking for Society National Bank -- Chapter 9 Programming: The Third Dimension -- Chapter 10 Programming Processes for Military Health Care Facilities -- Chapter 11 The Fit-Up for the World Headquarters of British Petroleum Company pic -- Chapter 12 Facility Master Plan for Mattel Toys Worldwide Headquarters -- Chapter 13 A Facility Planning Framework for Programming the Office Environment -- Chapter 14 Planning for a Captive Audience: Approaches and Problems in Programming Correctional Facilities -- PART III: ISSUES IN FACILITY PROGRAMMING -- Chapter 15 The Impact of the Client Organization on the Programming Process -- Chapter 16 The Role of the Programmer as Interpreter and Translator -- Chapter 17 Creating Decision-Support Systems -- Chapter 18 Research-Based Programming and Design -- Chapter 19 Programming for Safety -- Chapter 20 Programming Architectural Security in Facilities -- Chapter 21 Programming Considerations for Energy Conservation, -- Epilogue -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Architectural design -- Research; Architectural design -- Data processing; Electronic books